2015
DOI: 10.1111/jwas.12181
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fish Meal Replacement by a Soybean Protein on Growth, Histology, Selected Immune and Oxidative Status Markers of Gilthead Sea Bream, Sparus aurata

Abstract: The purpose of the trial was to study the impact of a 6‐mo dietary administration of soybean protein on growth, liver and intestine morphology, immune response, and oxidative stress in gilthead sea bream. The immune response was evaluated by performing immunological assays in blood, head kidney (HK), or serum (respiratory burst activity [RBA], myeloperoxidase content and bacteriolytic activity) and gene expression analysis of immune‐associated genes (MHCIIα [major histocompatibility complex IIα], β2m [β‐2‐micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
47
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 67 publications
4
47
0
2
Order By: Relevance
“…Plant proteins and poultry by-products have been tested for their appropriate inclusion level in diets for a variety of aquaculture species [2022]. The phenotypic responses, including growth performance and body composition have been characterized extensively.…”
Section: Introductionmentioning
confidence: 99%
“…Plant proteins and poultry by-products have been tested for their appropriate inclusion level in diets for a variety of aquaculture species [2022]. The phenotypic responses, including growth performance and body composition have been characterized extensively.…”
Section: Introductionmentioning
confidence: 99%
“…Ultimately, this study supports the use of this commercial blend of PEOs in low‐FM diets to decrease feed costs with FM, without compromising sea bass overall performance, nutrient utilization, and health. The negative implications that are usually associated with FM replacement by vegetable sources, such as intestinal morphology alterations (Bakke‐McKellep, Press, Baeverfjord, Krogdahl, & Landsverk, ; Rimoldi et al, ; Sanden, Berntssen, Krogdahl, Hemre, & Bakke‐McKellep, ) and immune response efficiency (Kokou et al, ), were neutralized with the supplementation of Digestarom PEP MGE 150 (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…While some studies have shown the successful replacement of FM and FO with plant‐based products in sea bream and sea bass feed, several problems have been identified, including reduced growth, feeding, and nutrient utilization (Montero, Robaina, Caballero, Ginés, & Izquierdo, ; Peres & Oliva‐Teles, ; Santigosa et al, ; Torrecillas et al, ). Moreover, plant‐based ingredients have also resulted in irregular fish gut morphology and physiology, followed by metabolic and digestive disorders (Guerreiro, Couto, Pérez‐Jiménez, Oliva‐Teles, & Enes, ; Kokou et al, ; Torrecillas, Robaina, et al, ). To overcome these issues, research has been focused on supplementation through functional dietary supplements, such as phytogenics (Karásková, Suchý, & Straková, ; Reverter, Bontemps, Lecchini, Banaigs, & Sasal, ; Sutili et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the use of algae as alternative diets have included evaluation of the use of Novacq, a novel ingredient of marine microalgae and bacteria in black tiger shrimp, Penaeus monodon (Sellars et al ), and heterotrophic algae meal in channel catfish diets (Kupchinsky et al ). Various products developed from soybeans have been evaluated, including a soybean protein in gilthead sea bream, Sparus aurata (Kokou et al ); hydrolyzed soy protein in starry flounder, Platichthys stellatus (Song et al ); soy protein concentrate for Nile tilapia, Oreochromis niloticus (Ribeiro et al ); soy peptide in juvenile Japanese flounder, Paralichthys olivaceus (Ragaza et al ); and a gamma‐irradiated and fermented soybean meal in juvenile Caspian brown trout, Salmo trutta caspius (Sotoudeh et al ). Other protein sources evaluated have included tuna byproduct meal in juvenile abalone, Haliotis discus (Jung et al ); grain distiller's dried yeast in rainbow trout, Oncorhynchus mykiss (Sealey et al ), and in juvenile Pacific white shrimp, Litopenaeus vannamei (Achupallas et al ); glandless cottonseed protein in Pacific white shrimp (Siccardi et al ); and cricket meal in African catfish, Clarias gariepinus (Taufek et al ).…”
mentioning
confidence: 99%